Transformacja Sił Zbrojnych RP 1999-2014. Aspekt finansowy - Korolczuk, Adam (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2016)
The last decade of 20th century as well as last 15 years were two frames of time where armed forces went under major transformation. Since 1999 almost all fields of regulations in Polish Army has been changed: organizational culture, professionalization of staff, drafting of women, procedures, technologies, armament and training. In spite of the above, some changes are still under debate, concerning mainly organizational structures, economic and political conditioning of its functioning. Transformation in military aspect has a special meaning, and due to universal coverage it is interpret in many different ways. Colloquially transformation identifies change and alteration, therefore we can differentiate political or system transformation and on the other hand military or Armed Forces. The objective of this article is to describe transformation process of the Polish Armed Forces, since Poland became a member of the North Atlantic Treaty Organization, indication of important changes concerning professionalization, budget structure, financing and military expenditures of the Ministry of National Defense, as well as analysis of technical modernization process.